Electrical and chemical stability engineering of solution-processed indium zinc oxide thin film transistors via a synergistic approach of annealing duration and self-combustion process. Issue 12 (15th August 2017) - Kim, Da Eun; Cho, Sung Woon; Kim, Young Been; Kim, Kyung Su; Yoon, Dea Ho; Jung, Sung Hyun; Kang, Won Jun; Cho, Hyung Koun
Abstract: The electrical and chemical stability of solution-processed indium zinc oxide (IZO) channel thin-film transistors (TFTs) were engineered via a synergistic approach of annealing duration and self-combustion process. In particular, the amorphous IZO TFTs that were thermally treated at 400 °C for 3 h using the specific precursor combination to generate internal self-combustion energy showed the best electrical performance [high saturation mobility ( μ SAT )=2.7 cm 2 /V s] and stability [low threshold voltage shift (Δ V TH ) under positive bias stress of 10.5 V] owing to the formation of oxide films with excellent metal–oxide–metal (M–O–M) bonds, fewer impurities, and an amorphous phase compared to IZO TFTs using other precursor formulas and annealing times. Longer annealing times led to a saturated M–O bond ratio and crystallization via extreme thermal annealing, which induced electrical degradation (low μ SAT and high Δ V TH ) of IZO TFTs. In the wet chemical patterning of electrodes, conventional acidic and basic wet etchants cause severe damage to the surfaces of the IZO channels; thus, insufficiently annealed IZO TFTs exhibited considerable degradation in terms of their on-current level and mobility. Alternatively, the TFTs subjected to an excessively long-term thermal annealing showed only a moderate decrease in mobility with the formation of small nanocrystals.